1978
DOI: 10.1289/ehp.7826217
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac toxicities of antibiotics.

Abstract: Isolated heart muscle preparations are useful in the study of cardiac toxicities of drugs and environmental chemicals: such tissues allow assessment of chemical effects on heart muscle that is free from indirect in vivo influences that can mask or even accentuate cardiac responses measured in the intact animal. In the present study, left atria of guinea pigs were used to demonstrate a direct cardiac depressant effect of greater-than-therapeutic concentrations of several aminoglycoside antibiotics. The toxic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Adams et al observed that high concentrations of gentamicin, kanamycin, amikacin and sisomicin reduced isometric contractile tension of electrically driven left atria of guinea pigs. Besides, they discovered that gentamicin not only produced a negative inotropic effect in isolated heart muscle but also decreased contractile responses to several positive inotropic interventions [ 85 ].…”
Section: Antibiotics’ Toxicitymentioning
confidence: 99%
“…Adams et al observed that high concentrations of gentamicin, kanamycin, amikacin and sisomicin reduced isometric contractile tension of electrically driven left atria of guinea pigs. Besides, they discovered that gentamicin not only produced a negative inotropic effect in isolated heart muscle but also decreased contractile responses to several positive inotropic interventions [ 85 ].…”
Section: Antibiotics’ Toxicitymentioning
confidence: 99%